The mean life of CO2 in the Earth's atmosphere and the temperature increase over the 2050 horizon - Pacheco, José Antônio de Freitas (Cadernos de Astronomia, 2025)
In this work a toy model is presented describing the evolution of the CO2 level in the Earth’s atmosphere. Using present data on the CO2 emission resulting from the human activity and carbon stockage by mechanisms acting in the biosphere, the average lifetime of CO2 in the atmosphere was estimated to be 120 years. If the emission rate behavior observed in the last decades is maintained, our model predicts around 2050 a CO2 concentration of 513 ppm and a temperature increase of +2,6°C above the limit fixed by the Paris agreement.
Keywords: carbon cycle; global warming; carbon dioxide